Multicentric Castleman’s disease mimicking extrapulmonary tuberculosis - Odhiambo, Teddy Fredrick; Ali, Abdirahman Mohamed (International Journal Of Community Medicine And Public Health, 2024)
Castleman disease is a rare proliferative lymph node disease with distinct histopathological features that manifest without any obvious symptoms. In high HIV prevalent areas Castleman’s disease pose diagnostic difficulties due to resemblance with other etiologies of lymphadenopathy. We report a case of a 58-year-old man who presented with complain of generalized body malaise and easy fatigability. Examination findings revealed left posterior cervical and bilateral axillary lymphadenopathy with CT scan of the abdomen showing generalized lymphadenopathy. Excisional lymph node biopsy was done and histology findings confirmed multicentric Castleman’s disease. This case illustrates that Castleman’s disease though rare can easily be confused with mimics such as tuberculosis in HIV patients.